KARAKTERISTIK KEPEMIMPINAN DALAM ISLAM (KAJIAN HISTORIS FILOSOFIS ) SIFAT-SIFAT RASULULLAH - Sakdiah Sakdiah (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2016)
Islam is very careful in determining who will be an exemplary leader of the group that nourish and build a Muslim personality. One of the leaders who meet the quality like that, for all Muslims is the Prophet Muhammad. Appointment him as the messenger of Allah., That in addition to lead mankind is also for the entire universe. The personality of the Prophet Muhammad swt., As a man whose leadership is exemplary toughness him to become a person who is not influenced by the circumstances surrounding community that is still ignorance. Aspects of personality that is very prominent in him like honesty (Siddiq), which is a principle in life and life. Perfect personality possessed by the Holy Prophet. as the Messenger of God as praiseworthy and perfect personality, known as the properties required for the Messenger of God, which includes Siddiq, trust, sermons, and fathanah. In recorded history that the figure of the Prophet Muhammad. a role not only as a leader in one thing only, but as a leader in terms of life include political, economic, military, and propaganda.